A First-in-Human Phase 1 Study of LY3023414, an Oral PI3K/mTOR Dual Inhibitor, in Patients with Advanced Cancer - Bendell, Johanna C; Varghese, Anna M; Hyman, David M; Bauer, Todd M; Pant, Shubham; Callies, Sophie; Lin, Ji; Martinez, Ricardo; Wickremsinhe, Enaksha; Fink, Aaron; Wacheck, Volker; Moore, Kathleen N (Clinical cancer research, 2018)
The PI3K/mTOR pathway is frequently aberrated in cancer. LY3023414 is a potent and selective ATP-competitive inhibitor of class I PI3K isoforms, mTOR, and DNA-PK. Here we report the dose-escalation results of the first-in-human phase I study of LY3023414. A 3+3 dose escalation for once-daily and twice-daily oral dosing of LY3023414 was followed by an expansion cohort for CYP3A4 drug-drug interaction (DDI) assessment. The primary objective was to determine the recommended phase 2 dose (RP2D). Additional objectives included safety, pharmacokinetics/pharmacodynamics, and antitumor activity. Forty-seven patients with solid tumors received LY3023414 at once-daily (20-450 mg) or twice-daily dosing (150-250 mg). Dose-limiting toxicities were observed at 450 mg once-daily (thrombocytopenia, hypotension, hyperkalemia) in three of three patients, 250-mg twice-daily dosing (hypophosphatemia, fatigue, mucositis) in three of four patients, and in one of 15 patients at 200 mg twice-daily (nausea). Common related AEs included nausea (38%), fatigue (34%), and vomiting (32%) and were mostly mild or moderate. LY3023414 pharmacokinetics demonstrated dose-dependent increase in exposure with ≥ 90% target inhibition at doses ≥150 mg. DDI analysis demonstrated LY3023414 to be a weak inhibitor of CYP3A4. Durable partial response was observed in a patient with endometrial cancer harboring PIK3R1 and PTEN truncating mutations, and 13 additional patients (28%) had a decrease in their target lesions by up to 30%. LY3023414 has a tolerable safety profile and single-agent activity in patients with advanced cancers. The RP2D of LY3023414 monotherapy is 200 mg twice daily based on safety, tolerability, and pharmacokinetic/pharmacodynamic data. .